An in-depth mixed-methods approach to Ryan White HIV/AIDS care program comprehensive needs assessment from the Northeast Georgia Public Health District: The significance of patient privacy, psychological health, and social stigma to care. (April 2015) - Huff, Amber; Chumbler, Neale; Cherry, Colleen O'Brien; Hill, Miranda; Veguilla, Vic
Highlights: Introduces an anthropologically-informed mixed-method research strategy for Ryan White Programs needs assessment. Explores relationships among issues patient privacy, psychological health, social stigma, and the HIV treatment cascade. Presents district-level recommendations based around leverage points identified through analysis of qualitative data collected with providers and utilizers of services. Findings highlight key institutional and interpersonal dimensions of care related to the spatial organization of HIV services and resources, provider capacity and competency to work with PLWHA, and local discourses around HIV/AIDS and HIV testing. Abstract: We apply a social-ecological interpretive framework to understanding relationships among patient privacy, psychological health, social stigma, and continuity in care in the HIV treatment cascade in the rural southeastern US. This research was conducted as part of the 2013 comprehensive needs assessment for the Northeast Georgia Ryan White Consortium using an anthropologically informed mixed-methods design, and a deductive-inductive approach to thematic analysis of qualitative data obtained in interviews and focus groups with service providers and service utilizers. Our comprehensive needs assessment yielded two key components. First, we identified salient phenomena influencing introduction to, retention among, and satisfaction of patients in the Ryan White-coordinated treatment cascade in NE-GA. Second, we formulated actionable recommendations around leverage points identified in the current district-wide system of care. Results highlight spatial, institutional, and interpersonal aspects of the system of care that intersect around issues of patient privacy, psychological health, and social stigma. These intersections constitute pathways by which persons living with HIV are exposed to stigma and other negative social signals regarding their health status without sufficient access to behavioral health services. These negative issues, in turn, can erect significant barriers to long-term continuity in care.